1) 3x² = 0
x² = 0/3
x = 0
2) (x+1)(x-1) = 0
x² - x + x - 1 = 0
x² = 1
x1 = 1
x2 = -1
3)4x²-1=0
4x² = 1
x² = 1/4
x1 = 1/2
x2 = -1/2
4)3x² = 5x
3x² - 5x = 0
x(3x-5) = 0
x1=0
или
3x-5=0
3x=5
x2=5/3
5)4x²-4x+1=0
d = b²-4ac
d = (-4)² - 4*4*1 = 16-16=0, 1 корень
x = -b/2a
x = 4/8 = 1/2
6) x²-16x-17=0
d=b²-4ac
d=(-16)² -4*(-17)= 256+68=324> 0, 2к.
x1; 2= (-b±√d)/2a = (16±18)/2
x1=(16+18)/2= 17
x2=(16-18)/2= -1
7)0,3x²+5x=2
0,3x²+5x-2=0
d=b²-4ac
d=5²-4*0,3*(-2) = 25+2,4=27,4> 0, 2к.
x1; 2= (-b±√d)/2a = (-5±√27,4)/0,6
x1= (-5+√27,4)/0,6
x2= (-5-√27,4)/0,6
8) x²-4x+5=0
d= (-4)²-4*5=16-20= -4< 0, корней нет.
1) (18a-3a²)/(8a²-48a)=3a(6-a)/8a(a-6)=3a(-1)(a-6)/8a(a-6)=-3/8
2) (8p-40)/(15-3p)=8(p-5)/3(5-p)=8(-1)(5-p)/3(5-p)=-8/3
3) (4-x²)/(10-5x)=(2-x)(2+x)/5(2-x)=(2+x)/5=2/5+x/5=0.4+0.2x
4) (3x+6y)²/(5x+10y)=9(x+2y)²/5(x+2y)=9(x+2y)/5=1.8(x+2y)=1.8x+3.6y
5) (ax+bx-ay-by)/(bx-by)=(x(a+b)-y(a+b))/b(x-y)=(a+b)(x-y)/b(x-y)=(a+b)/b=a/b+1
6) (a²-6a+9)/(27-a³)=(a-3)²/(3-a)(9+3a+a²)=(a-3)²/(-1)(a-3)(9+3a+a²)= =(3-a)/(9+3a+a²)
7) (2a-2b)²/(a-b)=4(a-b)²/(a-b)=4(a-b)=4a-4b
8) (4c+12d)²/(c+3d)=16(c+3d)²/(c+3d)=16(c+3d)=16c+48d
9) (4x²-y²)/(6x-3y)²=(2x-3y)(2x+3y)/9(2x-y)²=(2x+y)/9(2x-y)
10) (ab-3b-2a+6)/(15-5a)=(b(a-3)-2(a-3))/5(3-a)=(a-3)(b-2)/5(3-a)= =(a-3)(b-2)/5(-1)(a-3)=(2-b)/5
Объяснение: